(3TaGA GdCSbGe aj RjGQI NjQ GdGfGes - (3Ydj Hf YHO GdcGaj Hf Ydj Hf JeGe GdSHcj GdCfUGQj GdNRQLj, CHh GdMSf, Jbqj GdOjf,J (B756 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi ef YdjfG HQShdg CeG HYO agPG cJGH SejJg TaGA GdSbGe ai RjGQI NjQ GdGfGe hQJHJg Ydi YTQI CHhGH GdChd ai GdCMGOjK GdhGQOI ai GdRjGOI s
(3BNQgG (B:s
(3jfJgi HHGH ai SDGd GdebYO GdebQH jhe GdbjGeI s
(3GdfSNI HgG MhGTs
(3cJHJ HYV ChQGbg HNW eZGjQs
(3HBNQg hQbI SeGY Ydi GdeDda hNWg HUMI GdSeGY Ke NW hdOg YHO GdhgGH Hf Ydi HbQGAJg Ydi hGdOg ef Chd GdcJGH Edi GdHGH GdQGHY SfI (B745(3g` s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs